2023
DOI: 10.1017/s0956536121000651
|View full text |Cite
|
Sign up to set email alerts
|

Nueva perspectiva sobre el sistema de organización territorial epiclásico en la región de Zacapu, Michoacán

Abstract: Resumen El período de aproximadamente tres siglos (600–900 d.C.), que corresponde al epiclásico, fue el escenario de una notable expansión de los asentamientos en la cuenca de Zacapu y sus alrededores. Si bien la zona parecía carecer de núcleos monumentales mayores equivalentes a los que se conocían en las regiones vecinas del Bajío o del sur de las tierras altas michoacanas, los trabajos recientes en la parte noroeste del Malpaís de Zacapu cambian esta concepción. Los datos proporcionados por medio del LiD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 42 publications
1
10
0
3
Order By: Relevance
“…The resumption of research as part of the Uacusecha Archaeological Project (2009-2019) was consistent with the questions raised by movements at the northern border, of which the Chichimeca migrations reported by the Relación were only the last episodes (Pereira 2016(Pereira , 2018. This return to Zacapu allowed us to re-examine previously obtained data and to consider them from the perspective of a longterm process.…”
Section: The Uacusecha Archaeological Projectsupporting
confidence: 63%
See 1 more Smart Citation
“…The resumption of research as part of the Uacusecha Archaeological Project (2009-2019) was consistent with the questions raised by movements at the northern border, of which the Chichimeca migrations reported by the Relación were only the last episodes (Pereira 2016(Pereira , 2018. This return to Zacapu allowed us to re-examine previously obtained data and to consider them from the perspective of a longterm process.…”
Section: The Uacusecha Archaeological Projectsupporting
confidence: 63%
“…New data from these sites have considerably improved the quality of information, as most of them were only very partially known. The extension and organization of a number of these sites could thus be reassessed by means of various computer-mapping operations (Dorison 2019;Forest et al 2020), combined with field campaigns conducted between 2015 and 2019 (Pereira et al 2016(Pereira et al , 2018b. The LiDAR data also located 44 new sites, only nine of which have been verified in the field so far.…”
Section: The Uacusecha Archaeological Projectmentioning
confidence: 99%
“…The present study—and subsequent archaeological works (see Pereira et al 2021)—raised the number of archaeological settlements observed in the area from 17 to 31. It also revealed that the majority of archaeological features (residential, civic, artisanal, and agrarian) are concentrated in the highlands and MZC (Figure 3).…”
Section: Resultsmentioning
confidence: 69%
“…Thereby, from the sixth to the ninth century, pre-Hispanic farmers seem to have favored the late Pleistocene malpaís landforms, with their patches of light and porous soils, to cultivate. From the tenth to the twelfth century, this trend seems to have remained broadly unchanged, but this point remains unclear because the area was largely abandoned at the time (see Pereira et al 2021). A switch seems to have taken place with the arrival of Tarascan farmers recolonizing and urbanizing the area in the mid-thirteenth century.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation